A sensitive colorimetric aptasensor for chloramphenicol detection in fish and pork based on the amplification of a nano-peroxidase-polymer1. Issue 16 (21st August 2015) - Gao, Huiju; Gan, Ning; Pan, Daodong; Chen, Yinji; Li, Tianhua; Cao, Yuting; Fu, Tian
<x xml:space="preserve">Abstract</x> A polymerase chain (PV) labeled gold colloid as a signal tag could greatly catalyze the H2O2-mediated oxidation of TMB leading to color development, which can be easily observed by the naked eye and quantified by UV spectroscopy.